INSTITUTIONAL ASPECTS OF ADVANCEMENT OF TRAINING IN PREVENTIVE DENTISTRY OF DEGREE-SEEKING STUDENTS IN TERMS OF MARTIAL LAW - Salіuk O.; Makarova, I. (SWorld-Ger Conference proceedings, 2022)
В роботі розглянуті можливості удосконалення процесу практичної підготовки здобувачів вищої освіти з терапевтичної стоматології в умовах воєнного стану шляхом використання інноваційних технологій. In the work there are considered possibilities of advance